2020
DOI: 10.1007/s00429-020-02102-w
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic treatment normalizes midbrain dopaminergic neuron increase after periaqueductal gray stimulation

Abstract: Background: Electrical stimulation of the dorsolateral periaqueductal gray (dlPAG) in rats has been shown to elicit panic-like behaviour and can be a useful tool for modelling anticipatory fear and agoraphobia. Methods: In this study, we further analysed our previous data on the effects of escitalopram (a selective serotonin reuptake inhibitor, SSRI) and buspirone (a 5-HT1A receptor partial agonist) on dlPAG-induced anticipatory fear behaviour in a rat model using freezing as a measure. We then used tyrosine h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We also did not detect Aβ deposition in the periaqueductal gray of 5xFAD mice, which contradicts the findings in a post-mortem AD brain study that observed senile plaques in the periaqueductal gray in 81% of samples ( Parvizi et al, 2000 ). The periaqueductal gray is a major component of brainstem that has pivotal roles in autonomic function, behavior, memory formation, and emotional response to aversive events ( Lim et al, 2008 ; Lim et al, 2010 ; Temel et al, 2012 ; Tan et al, 2020b ). The absence of Aβ deposition in the periaqueductal gray in 5xFAD mice might represent an inability to recapitulate the Aβ pathological characteristics of human AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also did not detect Aβ deposition in the periaqueductal gray of 5xFAD mice, which contradicts the findings in a post-mortem AD brain study that observed senile plaques in the periaqueductal gray in 81% of samples ( Parvizi et al, 2000 ). The periaqueductal gray is a major component of brainstem that has pivotal roles in autonomic function, behavior, memory formation, and emotional response to aversive events ( Lim et al, 2008 ; Lim et al, 2010 ; Temel et al, 2012 ; Tan et al, 2020b ). The absence of Aβ deposition in the periaqueductal gray in 5xFAD mice might represent an inability to recapitulate the Aβ pathological characteristics of human AD.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was conducted as previously described to evaluate locomotor function ( Lim et al, 2016 ; Tan et al, 2020b ). The test was conducted in an enclosed square arena (40 cm × 40 cm × 40 cm) in dim light condition (30 ± 5 lux).…”
Section: Methodsmentioning
confidence: 99%
“…After 21 days of CUS, animals were subjected to electrical stimulation (1 h daily HFS for two weeks; from CUS day [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and behavioral testing to assess anxiety, anhedonia, behavioral despair or antidepressant-like activities. Behavioral testing was conducted on specific days in weeks 4 and 5 of CUS (i.e., CUS day [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Stressors were applied continuously throughout the entire experiment except during the behavioral testing.…”
Section: Chronic Unpredictable Stress (Cus) Animal Model Of Depressionmentioning
confidence: 99%
“…Blood samples were collected on the day before the CUS procedure and after 1 h of HFS PrL on the day of sacrifice. The sucrose intake test was conducted after 3 weeks of CUS (on day [20][21][22] and at week 4 after HFS PrL (on day [30][31][32]. Animals were categorized as either susceptible or resilient to CUS-induced depression based on the sucrose intake test after week 3 of CUS.…”
Section: Experiments 1: Hfs Prl In Cus-susceptible and -Resilient Modelsmentioning
confidence: 99%
See 1 more Smart Citation